Corpo e identidades femininas: a intermediação das mídia - Castro, Ana Lúcia de [UNESP]; Prado, Juliana do (My University, 2012)
This article intends to contribute to a reflection about the relationship between the body, media and femininities, thus seeking to indicate some elements in order to clarify how the media currently interferes in this relationship, especially for the construction of female identity with the presentation of styles of femininity that are part of a particular body standard. In order to do so, we present a brief bibliographical debate on media issues, identity, discourse and power, electing as empirical choices examples of print media aimed at the female segment in Brazil and Barbie dolls.

Este artigo pretende colaborar para a reflexão acerca da relação entre corpo, mídia e feminilidades, buscando pontuar alguns elementos no sentido de iluminar a maneira como a mídia interfere, contemporaneamente, nesta relação, sobretudo no caso da construção da identidade feminina, com a colocação de estilos de feminilidade que se inscrevem num determinado padrão corporal. Para tanto, apresenta uma breve discussão bibliográfica relativa aos temas mídia, identidade, discurso e poder, tomando como recortes empíricos alguns exemplos da mídia impressa voltada ao segmento feminino no Brasil e a Boneca Bárbie.
Body and female identities: the intervention of mass media
Keywords: Body; Identity; Subjectification; Gender; Media; Barbie; Identidade; Culto ao corpo; Indústria cultural; Mídia; Revistas femininas; Gênero